Isolation and Molecular Characterization of Escherichia coli from Goat of Apparently Healthy and Clinical Cases - Abdullah, Abu Sayeed M; Khan, M Shahidur Rahman; Alam, Munirul; Haq, Farjana; Hassan, Jayedul (Bangladesh Journal of Microbiology, 2011)
The prevalence of E. coli in faecal sample of apparently healthy and clinical cases of goats was investigated. A total of 150 samples of which 90 from clinical cases and 60 from apparently healthy goat were examined. Among the samples examined, 65(72.22%) and 25(41.67%) were found to be positive for E. coli in clinical and healthy cases respectably. The banding pattern of chromosome of isolated E. coli from goats of apparently healthy and clinical cases was also carried out by Pulsed Field Gel Electrophoresis through which the clonal relation between the isolated E. coli was studied. Chromosomal banding pattern of E. coli from goat of apparently healthy cases from same and different location were found identical which indicates similar clonal origin of E. coli. On the other hand, banding pattern of E. coli chromosome from diseased goat of different location were found dissimilar which may be either due to difference in origin of E. coli clone or phage encoded chromosome which can muted E. coli isolates. Thus it can be concluded that Pulsed Field Gel Electrophoresis profile varies according to severity of the disease. Keywords: Goat; E. coli; Isolation; Molecular Characterization DOI: http://dx.doi.org/10.3329/bjm.v27i1.9162 BJM 2010; 27(1): 14-17